Neurodevelopmental Tics with Co-Morbid Functional Tic-like Behaviors: Diagnostic Challenges of a Complex Tourette Syndrome Phenotype - Andrea Eugenio Cavanna; Virginia Caimi; Elisa Capriolo; Matteo Marinoni; Gabriele Arienti; Anna Riva; Renata Nacinovich; Stefano Seri (Brain Sciences)
Background/Objectives: The co-morbidity between neurodevelopmental tics and functional tic-like behaviors (FTBs) in patients with Tourette syndrome (TS) is relatively under-investigated. The demographic and clinical characteristics of a large sample of patients with TS who presented with co-morbid FTBs (functional overlay) were assessed to raise awareness of this complex clinical presentation and to shed light on the differential diagnosis between the two conditions. Methods: We analyzed the clinical data of 63 patients (44 females, mean age 24 years, range 13–40) with pre-existing TS who (sub)acutely developed co-morbid FTBs (TS + FTBs) after the onset of the COVID-19 pandemic and compared them with 63 age- and gender-matched controls with TS (neurodevelopmental tics only). The diagnosis of co-morbid FTBs was validated by the European Society for the Study of Tourette Syndrome (ESSTS) criteria. Results: Complex vocal tics (p < 0.001), including coprolalia (p = 0.002), and self-injurious behaviors (p < 0.001), often as part of tic attacks (p < 0.001), were confirmed to be more commonly reported by the group of patients with TS + FTBs, who were also more likely to present with anxiety (p < 0.001) and other functional neurological symptoms (p < 0.001) compared to patients with TS. Conclusions: Patients with TS and co-morbid FTBs can pose significant diagnostic and treatment challenges. By systematically applying ESSTS criteria, we confirmed specific red flags for the diagnosis of functional overlay in patients with TS. The correct identification of this composite clinical phenotype plays a key role in preventing the misdiagnosis of treatment-resistant TS and implementing tailored treatment interventions.